Multi-Criteria Decision Making Using Additive Ratio Assessment in Digital Voice Recorder Selection System - Nurhasan Nugroho (STMIK Budi Darma, 2022)
Digital Voice Recorder has many uses, usually used for interviews, recording voices and songs, recording meeting results, and can be used for learning. Currently, various Digital Voice Recorder products have been circulating and have different functions and specifications that are created according to the needs of users. For this reason, users must be observant in choosing a Digital Voice Recorder to support their work. So, we need a system that can provide recommendations and help in making decisions to choose the right Digital Voice Recorder. This study aims to develop a decision support system with Multiple Criteria Decision Making (MCDM) using Additive Ratio Assessment (ARAS) to assist in selecting a Digital Voice Recorder, so that it can assist in selecting the best solution appropriately and according to user needs. The ARAS method is used as a model that can select the best alternative based on the utility level of each alternative to determine the best alternative. Based on the case studies conducted, the utility values of each alternative were obtained, namely: Zoom Handy Recorder with a value of 0.5672, Sony PX470 with a value of 0.6147, Ruizu X52 with a value of 0.4664 and Tascam DR-22ML with a value of 0.9096. So, the best alternative is the Tascam DR-22ML. Based on testing through the black-box testing method, it shows that the system built has been running well